2013
DOI: 10.1007/s11274-013-1298-0
|View full text |Cite
|
Sign up to set email alerts
|

Detergent compatible alkaline lipase produced by marine Bacillus smithii BTMS 11

Abstract: Bacillus smithii BTMS 11, isolated from marine sediment, produced alkaline and thermostable lipase. The enzyme was purified to homogeneity by ammonium sulfate precipitation and ion exchange chromatography which resulted in 0.51 % final yield and a 4.33 fold of purification. The purified enzyme was found to have a specific activity of 360 IU/mg protein. SDS-PAGE analyses, under non-reducing and reducing conditions, yielded a single band of 45 kDa indicating the single polypeptide nature of the enzyme and zymogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 47 publications
1
44
0
1
Order By: Relevance
“…Evidence of an additional lipase secreted by P. solitum is noteworthy, because it supports the suggestion that penicillia are capable of producing more than one extracellular lipase. 37,38) Microbial lipases can act in a wide range of pH, even though the pH optimum for bacterial enzymes is usually neutral [39][40][41] or alkaline, 8,[42][43][44][45][46] and the pH optimum of fungal enzymes is in a range 4.0-8.0. 3) Maximal hydrolytic activity also depends on the type of ester used as substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of an additional lipase secreted by P. solitum is noteworthy, because it supports the suggestion that penicillia are capable of producing more than one extracellular lipase. 37,38) Microbial lipases can act in a wide range of pH, even though the pH optimum for bacterial enzymes is usually neutral [39][40][41] or alkaline, 8,[42][43][44][45][46] and the pH optimum of fungal enzymes is in a range 4.0-8.0. 3) Maximal hydrolytic activity also depends on the type of ester used as substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the pH 10.0 was optimum for the alkaline lipases purified from various Bacillus species (Lesuisse et al 1993;Bora & Kalita 2008;Bora & Bora 2012). pH 8.0 and 9.0 were also optima for lipases of Bacillus species (Sharma et al 2002;Chakraborty & Raj 2008; Anna- Shariff et al 2011;Lailaja & Chandrasekaran 2013). An important lipolytic activity was seen in the alkaline region from pH 7.0 to 13.0 (Fig.…”
Section: Determination Of Molecular Weight By Lc-msmentioning
confidence: 94%
“…Many lipases from Bacillus species have been purified to homogeneity (Lesuisse et al 1993;Sharma et al 2002;Kambourova et al 2003;Chakraborty & Raj 2008;Annamalai et al 2011;Shariff et al 2011;Bora & Bora 2012;Kumar et al 2012;Sharma & Kanwar 2012;Lailaja & Chandrasekaran 2013). Gupta et al (2004) reported that the purification must be efficient, fast, allowing the continuous recovery of a product and cost effective.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations